Home-Based Enrichment Activities for Science 9 (Biology): Effects on Students’ Academic Performance and Science Engagement - Antipatia, Jade Mark L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aimed to develop Home-Based Enrichment Activities specifically designed for Science 9 and assess their impact on academic performance and engagement of Grade 9 students attending public high schools in the Philippines during the first quarter of the school year 2022-2023. This study employed both descriptive and quasi-experimental research methods. The instruments included the validated pre-test and post-test assessments, a survey questionnaire for teachers, and a survey sheet for students. The data was collected from (60) students, (15) high school teachers and (15) master teachers in science in public schools. The data gathered were statistically analyzed using weighted mean, percentage, independent-samples t-Test, paired t-Test, and z-Test. Results showed that the control group exhibited lower mean scores (4.33 and 29.33) in the pretest and posttest compared to the experimental group (13.97 and 38.20), indicating a significant improvement in performance of the students, further affirming the positive impact of the developed Home-based enrichment activities on academic performance. The experimental group also expressed a high level of science learning engagement, demonstrating strong involvement, effort, and preparation in science lessons as manifested by the grand weighted mean of 3.88. Recommendations include incorporate home-based enrichment activities into blended learning modalities, particularly in modular distance learning to help students to learn the lesson and answer their modules on their own and increase students’ achievement in Science. Additionally, these supplementary activities can also provide valuable support to students who are at risk of failing a specific subject due to time constraints and challenging learning tasks within their modules.